Clinico-hematological study of urban malaria in patients attending a tertiary care center in India - Mukkamala, Subrahmanya Bharadwaj; Priyanka, Akella L. N.; Sivanand, Akella L. S.; Vardhan, Y. Vishnu (International Journal Of Community Medicine And Public Health, 2025)
Background: Malaria is a life-threatening disease, and it accounts for 7.8% of deaths in children globally. Changes in the hematological parameters are also believed to serve as supporting evidence in the suspicion of malaria during diagnosis. When combined with microscopy, a hematological profile will allow for quick diagnosis, efficient treatment, and prevention of subsequent issues. The aim was to evaluate malaria parasitemia and its relationship with clinico-hematological parameters in urban patients. Methods: An observational retrospective study of 78 cases of malaria in urban population were studied from the medical records of 3 years collected from a tertiary care centre in Visakhapatnam, after getting IHEC approval. All the patients admitted with diagnosed malaria were included, and their comprehensive clinical, demographic, and haematological data were noted. Results: In the 78 patients, 53.8% showed Plasmodium falciparum infection, 35.9% showed vivax and 10.3% had mixed infection. Anemia was seen in 57 subjects (73.1%), and severe anemia was noted in 17 cases. Thrombocytopenia was observed in 57.7% of them, and raised PT was seen in 65.4% cases. MCV and MCHC values were decreased in 32, and 36 subjects, whereas leukocytosis was seen in 27 cases. Falciparum malaria was significantly associated with thrombocytopenia, leukocytosis, and severe anemia in our study. Conclusions: Plasmodium falciparum malaria is a serious threat and has shown significant hematological alterations. To identify the complications early and to provide appropriate treatment, it is essential to understand the hematologic and biochemical alterations.